(untitled) (Revista científica Olimpia, 2019)
In the present investigation, a prospective longitudinal study was carried out to determine the behavior of the average hemoglobin values ​​of the school athletes of both sexes of the EIDE "Pedro Batista" of the Granma province in the Macrocycle of preparation 2014 - 2015. The universe consisted of 542 athletes, (279 male and 263 female). Measurements were made at the beginning of the Final General Physical Preparation of the General Physical Preparation and the End of the Special Physical Preparation. The blood sample was taken on an empty stomach and the cyanometahemoglobin method was used to determine hemoglobin. The data were processed through the statistical system SPSS 24.0 for Windows and were represented in double entry tables. It turned out that the average value of hemoglobin in the sports groups reflected, in Combat, the male sex of 13.1 g / dl and the female sex 12.2 g / dl, Games with Ball 13.2 g / dl in the male sex and 12.4 g / dl in the feminine, the group of Time and Marks the average values ​​were of 13.4 g / dl in the masculine sex and 12.7 g / dl in the feminine one and in Competitive Art, in the masculine sex average values ​​of 13.0 g / dl and in the female 12.5 g / dl. These results constitute a tool for sports-related specialists at early ages, providing data that allows them to unify criteria in the diagnosis of anemia in school athletes.